2015
DOI: 10.1016/j.ebiom.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Host-dependent Induction of Transient Antibiotic Resistance: A Prelude to Treatment Failure

Abstract: Current antibiotic testing does not include the potential influence of host cell environment on microbial susceptibility and antibiotic resistance, hindering appropriate therapeutic intervention. We devised a strategy to identify the presence of host–pathogen interactions that alter antibiotic efficacy in vivo. Our findings revealed a bacterial mechanism that promotes antibiotic resistance in vivo at concentrations of drug that far exceed dosages determined by standardized antimicrobial testing. This mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 57 publications
2
64
0
1
Order By: Relevance
“…The current study extends our previous work on the ability of NaHCO 3 supplementation of standard MRSA in vitro media to identify a sub-set of MRSA strains that may, in fact, exhibit β-lactam susceptibility (14, 22, 23). The notion of employing alternative media for antibiotic susceptibility screening is not new; however, the biological basis and clinical utility of this approach has substantially increased in the last few years.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The current study extends our previous work on the ability of NaHCO 3 supplementation of standard MRSA in vitro media to identify a sub-set of MRSA strains that may, in fact, exhibit β-lactam susceptibility (14, 22, 23). The notion of employing alternative media for antibiotic susceptibility screening is not new; however, the biological basis and clinical utility of this approach has substantially increased in the last few years.…”
Section: Discussionsupporting
confidence: 70%
“…For example, Kubicek-Sutherland et al mimicked the intracellular conditions of the macrophage phagosome in which Salmonella resides, using a mildly acidic and phosphate/magnesium-poor culture medium. Their study revealed that when Salmonella were grown in this media, antimicrobial susceptibility profiles emerging from this scenario were better predictors of treatment outcomes in murine bacteremia models than more traditional susceptibility testing strategies (23). Similar studies using Acinetobacter and staphylococci grown in Dulbecco Modified Eagles Medium (DMEM) or RPMI were better predictors of in vivo treatment outcomes, when compared to standard susceptibility testing modalities (13, 15).…”
Section: Discussionmentioning
confidence: 99%
“…56,57 The host–pathogen interactions involved in the transition of S. aureus from a commensal organism to an invasive pathogen are complex and not yet fully characterized. It is known that host AMPs provide a significant barrier to S. aureus colonization in humans.…”
Section: Resultsmentioning
confidence: 99%
“…All of these components modulate various pathways and are mainly causative for the altered in vivo efficiency of antibiotics. [69,[71][72][73][74] Efforts were made to mimic in vivo conditions during in vitro AST to account for this contextual antibiotic susceptibility.Astraightforward and very effective approach is the substitution of common rich laboratory medium with minimal medium. [75,76] Ar ecent study by Ersoy et al revealed that the antibiotic susceptibility of various clinical isolates strongly depends on the medium used for in vitro cultivation.…”
Section: Screening Platformsmentioning
confidence: 99%